The Value of Localizing Subclinical Seizures. Issue 3 (May 2020) - King-Stephens, David
Localization Value of Subclinical Seizures on Scalp Video-EEG in Epilepsy Presurgical Evaluation Wang Shan, Wang ZI, Tangy Y, et al. Epilepsia. 2019;60(1):2477-2485. doi:10.1111/epi.16383 . Objective: To evaluate the localization value and prognostic significance of subclinical seizures (SCSs) on scalp video electroencephalography monitoring (VEEG) in comparison to clinical seizures (CSs) in patients who had epilepsy surgery. Methods: We included 123 consecutive patients who had SCSs and CSs during scalp VEEG evaluation. All patients had subsequent epilepsy surgery and at least 1-year follow-up. Concordance between SCSs and CSs was summarized into 5 categories: complete, partial, overlapping, no concordance, or indeterminate. Using the same scheme, we analyzed the relationship between resection and SCS/CS localizations. The concordance measures, along with demographic, electroclinical, and other presurgical evaluation data, were evaluated for their associations with postoperative seizure outcome. Results: Sixty-nine (56.1%) patients had seizure-free outcome at 1-year follow-up. In 68 (55.3%) patients, the localizations of SCSs and CSs were completely concordant. Multivariate logistic analysis showed that complete SCS/CS concordance was independently associated with seizure-free outcome at 1 year ( P = .020) and 2-year follow-up ( P = .040). In the temporal lobe epilepsy (TLE) seizure-free group, SCS localization was completely contained within the resection in 44.4% and CS localization was completely contained within the resection in 41.7%; in the extratemporal lobe epilepsy (ETLE) seizure-free group, SCS localization was completely contained within the resection in 54.5% and CS localization was completely contained within the resection in 57.6%. Significance: Complete concordance between CS and SCS localization is a positive prognostic factor for 1-year and 2-year postoperative seizure-free outcome. Localization value of SCSs on scalp VEEG is similar to that of CSs for TLE and ETLE. Although SCSs cannot replace CSs, localization information from SCSs should not be ignored.